2001
DOI: 10.1152/jn.2001.86.4.1937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Optic Flow in Motor Cortex and Area 7a

Abstract: Moving visual stimuli were presented to behaving monkeys who fixated their eyes and did not move their arm. The stimuli consisted of random dots moving coherently in eight different kinds of motion (right, left, up, downward, expansion, contraction, clockwise, and counterclockwise) and were presented in 25 square patches on a liquid crystal display projection screen. Neuronal activity in the arm area of the motor cortex and area 7a was significantly influenced by the visual stimulation, as assessed using an AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 39 publications
9
59
1
Order By: Relevance
“…However, our results are seemingly in contradiction with a couple of electrophysiological studies in monkeys: Merchant et al (2001), who reported that M1 neurons modulated their activity in response to optic flow stimuli in different directions, and Suminski et al (2009), who found that visual playback of reaching actions is enough to elicit directional tuning in M1 neurons. It is likely that the fMRI signal may be too crude to detect neuronal features that are seen in a minority of the neuronal population.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results are seemingly in contradiction with a couple of electrophysiological studies in monkeys: Merchant et al (2001), who reported that M1 neurons modulated their activity in response to optic flow stimuli in different directions, and Suminski et al (2009), who found that visual playback of reaching actions is enough to elicit directional tuning in M1 neurons. It is likely that the fMRI signal may be too crude to detect neuronal features that are seen in a minority of the neuronal population.…”
Section: Discussioncontrasting
confidence: 99%
“…The function of these neurons appear to be 'defense' related: monkeys (and humans) are exquisitely sensitive to visual, auditory and multisensory looming signals that indicate approaching danger [31][32][33] and microstimulation of the 'polysensory zone' elicits defensive-like movements [34]. Consistent with these findings, visual responses in the primary motor cortex are particularly sensitive to expanding 'looming-like' optic flow stimuli [35].…”
Section: Frontal and Prefrontal Corticesmentioning
confidence: 88%
“…Although the experiment was not designed to distinguish between neuronal tuning to direction of movement and tuning to direction or location of the target, the fact that the best tuning in individual LFPs was obtained by alignment to movement onset in most LFPs but also by alignment to cue signal for approximately one-third of the LFPs, hints at a more complex involvement of LFPs in the control of voluntary movements [for tuning without movement, see Georgopoulos et al (1989); for motor cortical responses to visual stimuli, see Merchant et al (2001)]. …”
Section: Discussionmentioning
confidence: 99%